2012
DOI: 10.1099/mic.0.052399-0
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and antigenic characterization of monomeric autotransporters of Haemophilus parasuis: an ongoing process of reductive evolution

Abstract: The genome of the highly pathogenic Haemophilus parasuis Nagasaki strain (serovar 5) was sequenced to 99 % completion. A genomic comparison with two other pathogenic serovar 5 H. parasuis strains identified six genes per genome (bmaA1-bmaA6) encoding b-barrel monomeric autotransporters, bmaA2 and bmaA3 being pseudogenes in at least one strain. The remaining encoded proteins were predicted to belong to the subtilisin (BmaA1 and BmaA4) and cysteine (BmaA5 and BmaA6) protease families. Allelic polymorphism was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The antibodies induced by H. parasuis commercial killed vaccine and infection were both detectable via the rApd ELISA (Fig. 3), which is consistent with the findings that autotransporters of H. parasuis were able to be expressed in in vitro culture as well as in in vivo infection of pigs [15]. In addition, Apd was present in 15 serotype reference strains and five non-typeable strains tested; thus, the rApd ELISA exhibited the potential to be used for antibody detection to determine vaccine immunity and serological diagnosis of Glässer’s disease regardless of the serotype of strains.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The antibodies induced by H. parasuis commercial killed vaccine and infection were both detectable via the rApd ELISA (Fig. 3), which is consistent with the findings that autotransporters of H. parasuis were able to be expressed in in vitro culture as well as in in vivo infection of pigs [15]. In addition, Apd was present in 15 serotype reference strains and five non-typeable strains tested; thus, the rApd ELISA exhibited the potential to be used for antibody detection to determine vaccine immunity and serological diagnosis of Glässer’s disease regardless of the serotype of strains.…”
Section: Discussionsupporting
confidence: 86%
“…Autotransporters consist of a cleavable N-terminal signal peptide, a functional passenger domain exposed to the outer membrane or released into the external environment, and a C-terminal region involved in the formation of a transmembrane pore [15]. In the present study, three autotransporter passenger domains of H. parasuis were determined to represent candidate antigens for H. parasuis indirect ELISA, with a monomeric a utotransporter p assenger d omain (Apd) being selected as the optimal antigen.…”
Section: Introductionmentioning
confidence: 99%
“… The importance of the PATR within the AT family. A. Alignment of the PATR sites of IcsA and five other ATs : EprS ( Q9HY75 ), ShdA ( Q9XCJ4 ), subtilisin‐type serine protease PrtS ( P 09489) from S erratia marcescens (Shikata et al ., ), subtilisin‐type serine protease BmaA1 ( H6T4K9 ) of H aemophilus parasuis (Pina‐Pedrero et al ., ) and NalP ( Q8GKS5 ). Accessions are U ni P rot KB IDs .…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of the usage of domains and motifs in all ATs within the UniProt Knowledgebase was also conducted by first identifying unique ATs using InterPro (Hunter et al, 2012) AT β-barrel identifiers IPR005546 and/or IPR006315 (7659 proteins). Figure 4B shows the different virulence A. Alignment of the PATR sites of IcsA and five other ATs: EprS (Q9HY75), ShdA (Q9XCJ4), subtilisin-type serine protease PrtS (P09489) from Serratia marcescens (Shikata et al, 1992), subtilisin-type serine protease BmaA1 (H6T4K9) of Haemophilus parasuis (Pina-Pedrero et al, 2012) and NalP (Q8GKS5). Accessions are UniProtKB IDs.…”
Section: Analysis Of the Patr Within The At Familymentioning
confidence: 99%
“…Whole orthologous comparisons between H. parasuis and other micro-organisms within the Pasteurellaceae family showed that the swine pathogens H. parasuis and Actinobacillus pleuropneumoniae occupy close positions in this phylogenetic analysis, suggesting that the two species are probably derived from a recent common ancestor (Xu et al , 2011). In addition, a comparative analysis of monomeric autotransporters from three serovar 5 invasive strains (SH0165, 29755 and Nagasaki) suggested a reductive evolutionary state for these genes (Pina-Pedrero et al , 2012). More recently, a genome comparison of a H. parasuis serovar 12 strain (ZJ0906) with the serovar 5 strains SH0165 and 29755 showed that gene rearrangements are frequent in this species (Li et al , 2013).…”
Section: Introductionmentioning
confidence: 99%